Biallelic Pathogenic Variants in TNNT3 Associated With Congenital Myopathy. (June 2021) - Calame, Daniel G.; Fatih, Jawid; Herman, Isabella; Akdemir, Zeynep Coban; Du, Haowei; Jhangiani, Shalini N.; Gibbs, Richard A.; Marafi, Dana; Pehlivan, Davut; Posey, Jennifer E.; Lotze, Timothy; Mancias, Pedro; et al.
Abstract : Objective: Pathogenic variants in TNNT3, the gene encoding fast skeletal muscle troponin T, were first described in autosomal dominant distal arthrogryposis type 2B2. Recently, a homozygous splice site variant, c.681+1G>A, was identified in a patient with nemaline myopathy and distal arthrogryposis. Here, we describe the second individual with congenital myopathy associated with biallelic TNNT3 variants. Methods: Clinical exome sequencing data from a patient with molecularly undiagnosed congenital myopathy underwent research reanalysis. Clinical and histopathologic data were collected and compared with the single reported patient with TNNT3 -related congenital myopathy. Results: A homozygous TNNT3 variant, c.481-1G>A, was identified. This variant alters a consensus splice acceptor and is predicted to affect splicing by multiple in silico prediction tools. Both the patient reported here and the previously published patient exhibited limb, bulbar, and respiratory muscle weakness from birth, which improved over time. Other shared features include history of polyhydramnios, hypotonia, scoliosis, and high-arched palate. Distal arthrogryposis and nemaline rods, findings reported in the first patient with TNNT3 -related congenital myopathy, were not observed in the patient reported here. Conclusions: This report provides further evidence for the association of biallelic TNNT3 variants with severe recessive congenital myopathy with or without nemaline rods and distal arthrogryposis. TNNT3 sequencing and copy number analysis should be incorporated into the workup of congenital myopathies.